Answer:
B. y=−5x+1152
Step-by-step explanation:
From my thinking don’t use this one because I’m not really answering 5-2=3=3
Answer:
$43351.30
Step-by-step explanation:
Answer:
- 6x² - 2x + 1
Step-by-step explanation:
Given
(2x³ - 4x² - 3x + 5) + (- 2x³ - 2x² + x - 4)
Both parenthesis are distributed by 1 thus just remove them
= 2x³ - 4x² - 3x + 5 - 2x³ - 2x² + x - 4 ← collect like terms
= - 6x² - 2x + 1
Answer:
B
Step-by-step explanation:
You can just move upper y equation and it will be:
6x+3(3x-5)=15
6x+9x-15=15
15x-15=15
15x=30
x=2